Application of Ginsenoside Rd in Periodontitis With Inhibitory Effects on Pathogenicity, Inflammation, and Bone Resorption - Zhou, Shuhui; Ji, Yaoting; Yao, Hantao; Guo, Haiying; Zhang, Zichen; Wang, Zijun; Du, Minquan (Frontiers in Cellular and Infection Microbiology, 2022)
Periodontitis is a worldwide oral disease induced by the interaction of subgingival bacteria and host response and is characterized by local inflammation, bone resorption, and tooth loss. Ginsenoside Rd (Rd) is a biologically active component derived from Panax ginseng and has been demonstrated to exert antibacterial and anti-inflammatory activities. This study aims to investigate the inhibitory efficiency of Rd towards Porphyromonas gingivalis (P. gingivalis), periodontal inflammatory response, and osteoclastogenesis in vitro and to further validate the results in a mouse periodontitis model, thus, evaluate the potential effects of Rd on the control and prevention of periodontitis. According to the results, Rd exerted excellent antibacterial activities against planktonic P. gingivalis, along with attenuating P. gingivalis virulence and inhibiting its biofilms. Meanwhile, the inflammatory cytokine production and osteoclastogenesis were remarkably inhibited by Rd both in vitro and in vivo. Furthermore, Rd efficiently ameliorated the subgingival P. gingivalis abundance and suppressed the alveolar bone resorption in vivo as well. In conclusion, Rd has the potential to be developed as a promising medication in the control and prevention of periodontitis.